2019
DOI: 10.3390/pharmaceutics11020085
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Dihydropyridine Antihypertensive Drugs: Recent Advances in Photostabilization Strategies

Abstract: The 1,4-dihydropyridine (DHP) drugs are nowadays the most used drugs in the treatment of hypertension. However, all the structures in this series present a significant sensitivity to light, leading to the complete loss of pharmacological activity. This degradation is particularly evident in aqueous solution, so much so that almost all DHP drugs on the market are formulated in solid preparations, especially tablets. The first and main process of photodegradation consists in the aromatization of the dihydropyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…It is known from the literature that some 1,4-DHP molecules exhibit a significant sensitivity to light, leading to the complete loss of pharmacological activity [47,48]. It is necessary to emphasize that the tested cationic moieties containing 1,4-DHP are more stable than the corresponding parent compounds without cationic moieties.…”
Section: Synthesis Of 14-dhp Derivativesmentioning
confidence: 99%
“…It is known from the literature that some 1,4-DHP molecules exhibit a significant sensitivity to light, leading to the complete loss of pharmacological activity [47,48]. It is necessary to emphasize that the tested cationic moieties containing 1,4-DHP are more stable than the corresponding parent compounds without cationic moieties.…”
Section: Synthesis Of 14-dhp Derivativesmentioning
confidence: 99%
“…Ghosh et al reported a highly efficient, rapid and environment-benign protocol for the synthesis of Hantzsch 1,4dihydropyridine (18) under visible light irradiation via a onepot three-component reaction of aldehydes (15), ethyl acetoacetate ( 16) and ammonium hydroxide (17) in aqueous ethanol with excellent yields (92 %) (Scheme 9). [32] According to the suggested mechanism, a radical anion 10 A was formed by an electron transfer from ammonia (17) to the carbonyl group of ethyl acetoacetate (16) in the presence of light.…”
Section: Synthesis Of Dihydropyridine Derivativesmentioning
confidence: 99%
“…amlodypiny, felodypiny, nikardypiny, nifedypiny, nisoldypiny, m.in. poprzez zastosowanie liposomów z niejonowymi surfaktantami, utworzenie emulsji O/W z polioksyglicerydowymi emulgatorami i dekstrynami [19]. Procedury analityczne do monitorowania fotodegradacji leków z grupy chemicznych pochodnych DHP zostały przedstawione w wielu publikacjach naukowych, między innymi przy wykorzystaniu spektrofotometrii z zakresu UV-Vis oraz analizy danych wielowymiarowych [20].…”
Section: Fotodegradacja Substancji Leczniczychunclassified